Sistem Informasi Geografis Penyebab Pneumonia Dalam Menurunkan Angka Kematian Bayi Di Kabupaten Pangkep - Fania Gerda Rensiana; A. Rizki Amelia; A. Muhammad Multazam (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
This study aims to determine the relationship between exclusive breastfeeding and infant nutritional status in the Baring Community Health Center (Puskesmas Baring) working area. The research design used was quantitative with a cross-sectional approach. The study population was all mothers with infants aged 6–12 months, with a sample of X respondents selected purposively. Data were collected through interviews using questionnaires and infant weight measurements, then analyzed using the Chi-square test. The results showed a significant relationship between exclusive breastfeeding and infant nutritional status (p < 0.05). These findings confirm that infants who receive exclusive breastfeeding have a greater chance of achieving good nutritional status than infants who are not exclusively breastfed. Therefore, it is recommended that health workers increase educational and promotional efforts regarding the importance of exclusive breastfeeding, and equally important, encourage active family participation in supporting breastfeeding practices to achieve optimal infant growth and development.